Karakteristik Fisikokimia dan Stabilitas Antioksidan Ekstrak Ubi Jalar Ungu (Ipomoea batatas L.) - Tagor M Siregar; Fandy Kusno (The University of Lampung, 2026)
Purple sweet potatoes are known to contain a natural pigment and antioxidant called anthocyanins, whose stability is affected by pH and temperature. This study aimed to determine the physicochemical characteristics of extracts from different purple sweet potato (PSP) varieties and to evaluate the antioxidant stability of the extracts under various pH and temperature conditions. The PSP powders from three varieties—Bogor, Cilembu, and Murasaki (Japan) were extracted using the maceration method with 70% and 96% ethanol. The stability of the selected extract was tested at pH levels of 1, 3, 5, 7, and 9, and temperatures of 20, 40, 60, and 80°C. Results showed that variety significantly affected extract yield, water content, antioxidant activity, and total anthocyanin, phenolic, and flavonoid contents. The Bogor variety extracted with 96% ethanol yielded the best results, with 15.70±1.40% yield, 14.10±0.15% water content, 185.23±3.95 mg Fe²⁺/g antioxidant activity, 5.26±0.35 mg CyE/g anthocyanin, 40.35±3.87 mg GAE/g phenolic, and 5.12±1.05 mg QE/g flavonoid content. Increasing pH enhanced antioxidant activity and lightness, while color intensity decreased. Increasing temperature raised anthocyanin content and color parameters but reduced antioxidant activity. Under pH 1 and 80°C, the extract showed the highest anthocyanin content (6.01±0.44 mg CyE/g), a* (12.57±0.63), b* (0.73±0.06), and chroma (12.59±0.63) values.